ORAL N-ACETYL CYSTEINE VERSUS RECTAL INDOMETHACIN FOR PREVENTION OF POST ERCP PANCREATITIS: A MULTICENTER MULTINATIONAL RANDOMIZED CONTROLLED TRIAL - ALAVINEJAD,Pezhman (2022)
ABSTRACT Background This multicenter multinational RCT designed to compare the efficacy of suppository indomethacin and NAC for prevention of PEP. Methods: During a 6-month period, all of the ERCP cases in seven referral centers were randomly assigned to receive either 1200 mg oral NAC, indomethacin suppository 100 mg, 1200 mg oral NAC plus indomethacin suppository 100 mg or placebo 2 hours before ERCP. The primary outcomes were the rate and severity of any PEP. Results: A total of 432 patients included (41.4% male). They were originally citizens of 6 countries (60.87% Caucasian). They were randomly allocated to receive either NAC (group A, 84 cases), rectal indomethacin (group B, 138 cases), NAC + rectal indomethacin (group C, 115 cases) or placebo (group D, 95 cases). The rate of PEP in groups A, B and C in comparison with placebo were 10.7%, 17.4%, 7.8% vs 20% (P=0.08, 0.614 & 0.01 respectively). The NNT for NAC, indomethacin and NAC + indomethacin was 11, 38 and 8 respectively. Conclusion: Oral NAC is more effective than rectal indomethacin when compared to placebo for prevention of PEP and the combination of NAC and Indomethacin had the lowest incidence of PEP and may have synergistic effect in preventing of PEP (IRCT20201222049798N1; 29/12/2020).